Strategi Penguatan Literasi Moderasi Beragama Terintegrasi di Kabupaten Bandung Barat - Tojiri, Hamdan (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes that promotion of religious moderation education is a strategic response to the growing threats of intolerance and radicalism in various sectors of Indonesian society. In West Bandung Regency, efforts to build inclusive and tolerant education have yet to yield optimal results, as reflected in the limited public literacy on moderation values and the absence of policies that mainstream a holistic approach. This policy paper aims to formulate integrated strategies for the development of religious moderation education by identifying key opportunities, challenges, and regulatory-based policy alternatives. The study applies a qualitative-descriptive approach using William N. Dunn’s policy analysis model, which includes problem identification, formulation of alternatives, and evaluation of policy options. Data sources include statutory regulations, official publications from the Ministry of Religious Affairs, and relevant academic literature. Analysis is conducted through normative and institutional frameworks, aligning substantive issues in the field with existing legal instruments, including Law No. 20 of 2003 on the National Education System, the 2020–2024 National Medium-Term Development Plan (RPJMN), Presidential Instruction No. 7 of 2022, and Ministerial Decree No. 93 of 2022. The findings suggest that mainstreaming religious moderation should begin by integrating it into the strategic planning documents of regional religious offices, supported by technical teaching guidelines and the incorporation of moderation values across all subjects.